Transparent conductive film, laminate, and method for producing transparent conductive film

A transparent conductive film with a polycrystalline structure and specific grain size, manufactured through controlled sputtering and annealing, addresses durability issues in high-temperature and high-humidity environments, ensuring reliability without a gas barrier layer.

JP7605745B2Active Publication Date: 2024-12-24NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021550589
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-16
Publication Date
2024-12-24
Estimated Expiration
2040-09-16

AI Technical Summary

Technical Problem

Existing transparent conductive films lack durability in high-temperature and high-humidity environments, particularly when a gas barrier layer is not present, and existing technologies do not adequately address this issue.

Method used

A transparent conductive film with a polycrystalline structure having grains with an average maximum Feret diameter of 160 to 400 nm, manufactured by sputtering with an inert gas pressure of 0.4 Pa or less and annealing, which enhances durability without a gas barrier layer.

Benefits of technology

The film exhibits high durability in high-temperature and high-humidity environments, maintaining low water vapor permeability and resisting cracking, even without a gas barrier layer, suitable for applications in harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605745000002
    Figure 0007605745000002
  • Figure 0007605745000003
    Figure 0007605745000003
  • Figure 0007605745000004
    Figure 0007605745000004
Patent Text Reader

Abstract

This transparent electroconductive film 3 comprises a polycrystal 31. The polycrystal 31 has grains 32. The average value Df of the maximum Feret diameter of the grains 32 is 160-400 nm.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film, a laminate, and a method for producing a transparent conductive film. [Background technology]

[0002] Polycrystalline transparent conductive films have been known in the art.

[0003] For example, Patent Document 1 describes a substrate with a conductor, which has a transparent conductive film and a metal coating formed on a required portion of the transparent conductive film. <222> The crystal grain size in the direction is 400 Å or more. This provides strong adhesion between the transparent conductive film and the metal coating. In addition, the transparent conductive film is in a polycrystalline state.

[0004] On the other hand, a technology is known in which a gas barrier layer is used to prevent deterioration of a transparent conductive layer. For example, Patent Document 2 describes a transparent conductive film comprising a resin substrate, a gas barrier layer, and a transparent conductive layer. In the transparent conductive film, the gas barrier layer is formed between the resin substrate and the transparent conductive layer. The gas barrier layer suppresses the transmission of water vapor, thereby preventing deterioration of the transparent conductive layer. In a transparent conductive film, for example, a water vapor transmission rate of 0.1 g / m under high humidity conditions of 40°C and 90% RH is 0.1 g / m. 2 / day or less. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-151827 [Patent Document 2] JP 2014-201800 A Summary of the Invention [Problem to be solved by the invention]

[0006] According to the technology described in Patent Document 1, in the X-ray diffraction method for a transparent conductive film, <222> The crystal grain size in the direction is determined from the viewpoint of increasing the adhesive strength between the transparent conductive film and the metal coating, and Patent Document 1 does not consider at all the durability of the transparent conductive film in a high-temperature and high-humidity environment.

[0007] According to the technology described in Patent Document 2, a gas barrier layer is necessary to prevent deterioration of the transparent conductive layer.

[0008] In view of the above circumstances, the present invention provides a transparent conductive film having high durability in a high-temperature and high-humidity environment even in the absence of a gas barrier layer near the transparent conductive film, and also provides an advantageous method for producing such a transparent conductive film. [Means for solving the problem]

[0009] The present invention relates to The present invention provides a transparent conductive film comprising polycrystals, the polycrystals having grains with an average maximum Feret diameter of 160 to 400 nm.

[0010] The present invention also provides a method for producing a semiconductor device comprising the steps of: A substrate; The transparent conductive film is disposed on the substrate. A laminate is provided.

[0011] The present invention also provides a method for producing a semiconductor device comprising the steps of: forming a film on a substrate by sputtering; and annealing the film to form a transparent conductive film; In the sputtering, the pressure of the inert gas is adjusted to 0.4 Pa or less. A method for producing a transparent conductive film is provided. Effect of the Invention

[0012] The transparent conductive film has high durability in a high-temperature and high-humidity environment even when no gas barrier layer is present near the transparent conductive film. The method is advantageous for producing the transparent conductive film. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the laminate according to the present invention. [Diagram 2] FIG. 3 is a diagram showing a schematic structure of the film surface of the transparent conductive film shown in FIG. 2. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of a heater including a laminate according to the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing another example of a heater including a laminate according to the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing an example of a heater-equipped article equipped with the heater shown in FIG. [Figure 6] FIG. 6 is a diagram conceptually illustrating a method for measuring the internal stress of a transparent conductive film. [Figure 7A] FIG. 7A is a transmission electron microscope (TEM) photograph of the film surface of the transparent conductive film according to Example 1. [Figure 7B] FIG. 7B is a diagram showing boundaries between grains in the photograph shown in FIG. 7A. [Figure 8A] FIG. 8A is a TEM photograph of the film surface of the transparent conductive film according to Comparative Example 1. [Figure 8B] FIG. 8B is a diagram showing boundaries between grains in the photograph shown in FIG. 8A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] If the durability of the transparent conductive film in a high-temperature, high-humidity environment can be improved even if there is no gas barrier layer near the transparent conductive film, the value of the transparent conductive film will be further increased. For example, if such a transparent conductive film can be used in the fields of information terminals equipped with touch panels such as smartphones and heaters, high-value-added products can be provided. For example, since in-vehicle devices are required to function properly even in harsh environments, it is advantageous for the transparent conductive film to have durability even in harsh environments when used in in-vehicle devices. On the other hand, in the past, it was thought that in order to improve the durability of the transparent conductive film, it was necessary to provide a gas barrier layer near the transparent conductive film, as in the technology described in Patent Document 2. Therefore, the present inventors have conducted intensive research into a technology that can improve the durability of the transparent conductive film in a high-temperature, high-humidity environment even if there is no gas barrier layer near the transparent conductive film. As a result of extensive trial and error, the present inventors have newly discovered that the transparent conductive film having a predetermined polycrystal is advantageous in improving the durability of the transparent conductive film in a high-temperature, high-humidity environment. Based on this new discovery, the present inventors have finally completed the present invention.

[0015] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that the following description is for illustrative purposes only, and the present invention is not limited to the following embodiment. Note that in this specification, "transparent" typically means transparent to visible light.

[0016] 1, the laminate 1 includes a substrate 2 and a transparent conductive film 3. The transparent conductive film 3 is disposed on the substrate 2. Thus, the transparent conductive film 3 is typically provided in a state of being disposed on the substrate 2.

[0017] As shown in FIG. 2, the transparent conductive film 3 has polycrystals 31. The polycrystals 31 have grains 32. The average value Df of the maximum Feret diameter of the grains 32 is 160 to 400 nm. When the average value Df is 160 nm or more, water vapor is less likely to permeate the transparent conductive film 3, and the transparent conductive film 3 can exhibit high durability in a high-temperature, high-humidity environment even if a gas barrier layer is not present near the transparent conductive film 3. In addition, when the average value Df is 400 nm or less, cracks are less likely to occur in the transparent conductive film 3 even if the transparent conductive film 3 is subjected to bending stress. Therefore, the transparent conductive film 3 can exhibit high durability in a high-temperature, high-humidity environment. The average value Df can be determined, for example, according to a method including the following steps (I), (II), and (III). (I) In a TEM photograph of the film surface of the transparent conductive film 3, the boundaries between the grains 32 are determined based on the contrast difference between the images of adjacent grains 32 in a field of view of 400 nm square at 10 or more randomly selected locations. (II) Based on the boundaries determined in step (I), the maximum Feret diameter of each grain 32 included in each field of view is determined. This determination is performed for all grains 32 that are entirely visible in each field of view. (III) Based on the maximum Feret diameter of each grain 32 determined in step (II), the average value Df of the maximum Feret diameter of the grains 32 is determined by arithmetic averaging.

[0018] A predetermined durability test is performed on the transparent conductive film 3. In this case, the sheet resistance Rp [Ω / □] of the transparent conductive film 3 after the durability test and the sheet resistance Rb [Ω / □] of the transparent conductive film 3 before the durability test satisfy, for example, the relationship |Rp-Rb| / Rb≦5%. In other words, the rate of change in the sheet resistance of the transparent conductive film 3 before and after the durability test is, for example, 5% or less. The durability test is performed, for example, by maintaining the environment of the transparent conductive film 3 at a temperature of 85° C. and a relative humidity of 85% for 1000 hours. The sheet resistance of the transparent conductive film 3 is unlikely to change in a high-temperature, high-humidity environment, and the transparent conductive film 3 can exhibit high durability in a high-temperature, high-humidity environment. Note that the environmental conditions of the transparent conductive film 3 in the durability test are merely examples, and the relationship |Rp-Rb| / Rb≦5% can be satisfied even if a durability test is performed on the transparent conductive film 3 under other conditions generally required in the fields of information terminals equipped with touch panels such as smartphones and in-vehicle devices such as heaters. For example, with the transparent conductive film 3, even if durability tests are performed in a high-temperature, low-humidity environment, a low-temperature, high-humidity environment, and a low-temperature, low-humidity environment, the relationship |Rp-Rb| / Rb≦5% can be satisfied.

[0019] The average value Df may be 170 nm or more, 180 nm or more, 190 nm or more, or 200 nm or more. The average value Df may be 350 nm or less, 330 nm or less, 300 nm or less, 280 nm or less, or 250 nm or less.

[0020] The transparent conductive film 3 has a water vapor permeability Ws of a predetermined laminate determined in accordance with, for example, ISO 15106-5:2015 of 0.0010 to 0.0250 g / (m 2 The laminate is a laminate in which a transparent conductive film 3 is disposed on a support material. In addition, the water vapor transmission rate of the support material, determined according to ISO 15106-5:2015, is 1 g / (m 224 hours) or more. In this case, the transparent conductive film 3 can maintain a low water vapor permeability of the laminate produced by disposing the transparent conductive film 3 on a support material having a high water vapor permeability. Therefore, even if a gas barrier layer does not exist near the transparent conductive film 3, the transparent conductive film 3 can more reliably exhibit high durability in a high temperature and high humidity environment. Note that this laminate is produced for the sake of convenience in indirectly evaluating the water vapor permeability of the transparent conductive film 3, and when the laminate 1 is produced, the support is not superimposed on the substrate 2 in a state in which the transparent conductive film 3 is formed on the support. When the laminate 1 is produced, typically, the transparent conductive film 3 is formed alone on the substrate 2. The support material in this laminate may be the same as or different from the substrate 2 in the laminate 1. In other words, the value of the water vapor permeability of the substrate 2 determined in accordance with ISO 15106-5:2015 is 1 g / (m 2 The water vapor transmission rate of the substrate 2 is not limited to 1 g / (m 2 In this laminate, the support material occupies a different space from the transparent conductive film 3 and is clearly distinguished from the transparent conductive film 3.

[0021] The transparent conductive film 3 has a water vapor permeability Ws of preferably 0.0010 to 0.0200 g / (m 2 24 hours), and more preferably 0.0010 to 0.0150 g / (m 2 24 hours), and more preferably 0.0010 to 0.0120 g / (m 2 The water vapor permeability Ws is 0.005g / (m 2 24 hours) or more, and may be 0.008g / (m 2 -24 hours or more.

[0022] There is no particular limitation on the material that forms the polycrystals 31 in the transparent conductive film 3. The polycrystals 31 include, for example, indium oxide. This allows the transparent conductive film 3 to more reliably exhibit high durability in a high-temperature and high-humidity environment.

[0023] In the transparent conductive film 3, the polycrystals 31 preferably contain indium oxide as a main component. This is advantageous in terms of enabling the transparent conductive film 3 to exhibit high durability in a high-temperature and high-humidity environment. In this specification, the term "main component" refers to the component that is contained in the largest amount by mass.

[0024] In the transparent conductive film 3, the polycrystals 31 preferably contain indium tin oxide (ITO). This allows the transparent conductive film 3 to more reliably exhibit high durability in a high-temperature and high-humidity environment. The content of tin oxide in the ITO is, for example, 3 to 14% by weight, and preferably 5 to 13% by weight.

[0025] The density d of the transparent conductive film 3 is not limited to a specific value. The density d is, for example, 7.15 g / cm 3 In this case, the gaps between the grains 32 tend to become smaller in the polycrystals 31. As a result, water vapor is less likely to permeate the transparent conductive film 3, and the transparent conductive film 3 can more reliably exhibit high durability in a high-temperature and high-humidity environment.

[0026] The density d is 7.20 g / cm 3 or more, 7.30 g / cm 3 The density d may be, for example, 7.50 g / cm 3 As a result, cracks are less likely to occur in the transparent conductive film 3, and the transparent conductive film 3 can more reliably exhibit high durability in a high-temperature and high-humidity environment. 3 It may be the following.

[0027] The thickness t of the transparent conductive film 3 is not limited to a specific value. The thickness t is, for example, 20 to 150 nm. When the thickness t is 20 nm or more, the transparent conductive film 3 is likely to have a desired sheet resistance. On the other hand, when the thickness t is 150 nm or less, cracks are unlikely to occur in the transparent conductive film 3, and the transparent conductive film 3 can more reliably exhibit high durability in a high-temperature and high-humidity environment.

[0028] The thickness t may be 25 nm or more, 35 nm or more, or 45 nm or more. The thickness t may be 140 nm or less, 130 nm or less, or 120 nm or less.

[0029] The internal stress Pi of the transparent conductive film determined by X-ray stress measurement is not limited to a specific value. The internal stress Pi is, for example, 150 to 1000 MPa. When the internal stress Pi is 100 MPa or more, the gaps between the grains 32 in the polycrystal 31 tend to become small. As a result, water vapor is less likely to permeate the transparent conductive film 3, and the transparent conductive film 3 can more reliably exhibit high durability in a high-temperature, high-humidity environment. On the other hand, when the internal stress Pi is 1000 MPa or less, cracks are less likely to occur in the transparent conductive film 3, and the transparent conductive film 3 can more reliably exhibit high durability in a high-temperature, high-humidity environment. The internal stress Pi can be measured, for example, according to the method described in the examples.

[0030] The internal stress Pi may be 160 MPa or more, 180 MPa or more, 200 MPa or more, or 300 MPa or more. The internal stress Pi may be 950 MPa or less, 900 MPa or less, or 800 MPa or less.

[0031] In the laminate 1, the substrate 2 is not limited to a specific substrate. In particular, the water vapor transmission rate Wk of the substrate 2 determined in accordance with ISO 15106-5:2015 is not limited to a specific value. The water vapor transmission rate Wk is, for example, 1 g / (m 2 24 hours) or more. The water vapor permeability Wk is 1g / (m 2 - It may be less than 24 hours.

[0032] The substrate 2 is transparent to, for example, visible light. This allows the laminate 1 to also be transparent to visible light. The laminate 1 may be transparent to light of a predetermined wavelength, such as near-infrared light.

[0033] The material of the substrate 2 is not limited to a specific material. The substrate 2 contains an organic material such as an organic polymer. This makes the substrate 2 more flexible. The substrate 2 may contain at least one organic polymer selected from the group consisting of polyethylene terephthalate, polyethylene naphthalate, polyimide, polycarbonate, polyether ether ketone, and aromatic polyamide. The substrate 2 may contain an inorganic material such as glass. In this case, the laminate 1 is more likely to have high rigidity. The substrate 2 may be a hybrid of an organic material and an inorganic material, or may be a composite material.

[0034] For example, in the laminate 1, the substrate 2 and the transparent conductive film 3 are in contact with each other. The main surface 21 of the substrate 2 forming the interface with the transparent conductive film 3 may be formed of a material having gas barrier properties, or may be formed of a material having no gas barrier properties.

[0035] The thickness T of the substrate 2 is not limited to a specific value. From the viewpoints of good transparency, good strength, and ease of handling, the thickness T is, for example, 10 μm to 2 mm. The thickness T may be 20 μm or more, 30 μm or more, or 50 μm or more. The thickness T may be 1.8 mm or less, 1.5 mm or less, 1.0 mm or less, 500 μm or less, 300 μm or less, or 200 μm or less.

[0036] The following describes an example of a method for producing the transparent conductive film 3. The transparent conductive film 3 is produced, for example, by a method including the following steps (i) and (ii). (i) A film is formed on a substrate 2 by sputtering. (ii) Annealing the film to form a transparent conductive film 3.

[0037] In the sputtering of step (i), the pressure Pf of the inert gas is adjusted to 0.4 Pa or less. Conventionally, it has been considered that a low pressure of the inert gas when forming a transparent conductive film by sputtering is disadvantageous because the internal stress of the transparent conductive film increases and causes deformation of the substrate. However, according to trial and error by the present inventors, it has been found that adjusting the pressure Pf to 0.4 Pa or less in the sputtering for forming the transparent conductive film is advantageous in producing a transparent conductive film that exhibits high durability in a high-temperature and high-humidity environment. In the sputtering for forming the transparent conductive film, if the pressure Pf is adjusted to 0.4 Pa or less, it is considered that the ion particles collide with the substrate 2 while maintaining a high energy state. It is considered that this makes it easier to adjust the average value Df of the maximum Feret diameter of the grains 32 to a range of 160 to 400 nm.

[0038] The pressure Pf may be equal to or less than 0.35 Pa, or may be equal to or less than 0.3 Pa. The pressure Pf may be, for example, equal to or more than 0.05 Pa, equal to or more than 0.07 Pa, or may be equal to or more than 0.1 Pa.

[0039] The sputtering method in step (i) is not limited to a specific method. For example, the sputtering method in step (i) is a high magnetic field DC magnetron sputtering method. This makes it possible to more reliably manufacture a transparent conductive film 3 that exhibits high durability in a high temperature and high humidity environment.

[0040] The annealing in step (ii) promotes crystallization in the film formed in step (i), resulting in a desired state of polycrystals 31 in the transparent conductive film 3.

[0041] The environmental temperature Tk of the substrate 2 in the annealing step (ii) is not limited to a specific value. The environmental temperature Tk is, for example, 165° C. or higher. This makes it easier for the substrate 2 to shrink after annealing, and the internal stress of the transparent conductive film 3 to increase. As a result, it is possible to more reliably manufacture a transparent conductive film 3 that exhibits high durability in a high-temperature and high-humidity environment.

[0042] The environmental temperature Tk may be equal to or higher than 170° C., or may be equal to or higher than 175° C. The environmental temperature Tk is, for example, equal to or lower than 185° C. This makes it difficult for cracks to occur in the transparent conductive film 3.

[0043] The annealing time Ha in step (ii) is not limited to a specific value. The time Ha is, for example, 90 minutes or less. The time Ha may be 60 minutes or less. The time Ha is, for example, 15 minutes or more. This allows polycrystals 31 in a desired state to be obtained in the transparent conductive film 3.

[0044] The transparent conductive film 3 may be formed by a method other than sputtering, such as vacuum deposition or ion plating.

[0045] The laminate 1 can be used in the fields of, for example, touch panels and heaters for information terminals. For example, the laminate 1 can be used to provide a heater 10a shown in FIG. 3. The heater 10a includes the laminate 1 and a pair of power supply electrodes 4. The pair of power supply electrodes 4 is electrically connected to a transparent conductive film 3. The pair of power supply electrodes 4 can be connected to a power source (not shown). In this specification, the pair of power supply electrodes 4 means a pair of a positive electrode and a negative electrode. When one of the pair of power supply electrodes 4 acts as a positive electrode, the other of the pair of power supply electrodes 4 acts as a negative electrode. Power from a power source is supplied to the transparent conductive film 3 by the pair of power supply electrodes 4, and the transparent conductive film 3 generates heat.

[0046] The power supply electrode 4 has a thickness of, for example, 1 μm or more. This makes it difficult for the power supply electrode 4 to be broken when the heater 1a is operated at a high temperature rise rate. The thickness of the power supply electrode 4 is significantly larger than the thickness of an electrode formed on a transparent conductive film used in a display device such as a touch panel. The thickness of the power supply electrode 4 may be 2 μm or more, 3 μm or more, or 5 μm or more. The thickness of the power supply electrode 4 is, for example, 5 mm or less, 1 mm or less, or 700 μm or less.

[0047] The pair of power supply electrodes 4 are formed, for example, as follows. A seed layer is formed on the main surface of the transparent conductive film 3 by a dry process such as chemical vapor deposition (CVD) and physical vapor deposition (PVD) or a plating method. Next, a masking film is placed on the seed layer on which the power supply electrodes 4 should not be formed. The masking film can be produced by laminating a resist on the seed layer, followed by a process of exposure and development. Then, a metal film of 1 μm or more is formed on the portion on which the masking film is not placed by a wet process such as plating. Next, the masking film placed on the seed layer is removed, and the metal film to be the power supply electrodes 4 is covered with a masking film formed using the resist. Next, the exposed seed layer is removed by etching. Then, the masking film is removed, thereby forming the pair of power supply electrodes 4.

[0048] The pair of power supply electrodes 4 may be formed as follows. First, as described above, a seed layer is formed on the main surface of the transparent conductive film 3. Then, a metal film having a thickness of 1 μm or more is formed on the main surface of the transparent conductive film 3 by a dry process such as CVD and PVD or a wet process such as plating. Next, a part of the metal film to be the power supply electrodes 4 is covered with a masking film formed using a resist. Then, unnecessary metal film is removed by etching, and the masking film is removed. In this way, the pair of power supply electrodes 4 are formed. Furthermore, the power supply electrodes 4 may be formed by applying a conductive ink in a predetermined pattern on the main surface of the transparent conductive film 3 and curing the applied conductive ink. The power supply electrodes 4 may be formed by applying a conductive paste in a predetermined pattern on the main surface of the transparent conductive film 3 by a coating method such as coating with a dispenser or screen printing, and curing the applied conductive paste. The conductive paste typically contains a filler of a conductive material such as silver. The power supply electrodes 4 may be formed using a solder paste.

[0049] The heater 10a can be modified in various respects. For example, the heater 10a may be modified to a heater 10b shown in FIG. 4. The heater 10b is configured similarly to the heater 10a unless otherwise specified. The components of the heater 10b that are the same as or correspond to the components of the heater 10a are given the same reference numerals and detailed description is omitted. The description of the heater 10a also applies to the heater 10b unless there is a technical contradiction.

[0050] As shown in FIG. 4, the heater 10b includes a protective layer 5. The protective layer 5 is disposed so that the transparent conductive film 3 is located between the protective layer 5 and the substrate 2. The protective layer 5 includes, for example, a predetermined protective film and an adhesive layer that attaches the protective film to the transparent conductive film 3. The transparent conductive film 3 is protected by the protective layer 5, and the heater 10b has high impact resistance. The material of the protective film in the protective layer 5 is not particularly limited, but is, for example, a synthetic resin such as fluororesin, silicone, acrylic resin, and polyester. The thickness of the protective film is not limited to a specific value, but is, for example, 20 to 200 μm. This allows the heater 10b to have good impact resistance while preventing the heater 10b from becoming too thick. The adhesive layer is formed of a known adhesive such as an acrylic adhesive. For example, when the protective film itself has adhesiveness, the protective layer 5 may be formed only by the protective film.

[0051] An article with a heater can be provided using the heater 10a or 10b. For example, as shown in FIG. 5, an article with a heater 100 includes a molded body 7, an adhesive layer 6, and a heater 10a. The molded body 7 has an adhesion surface 71. The molded body 7 is formed of a metal material, glass, or synthetic resin. The adhesive layer 6 is in contact with the adhesion surface 71. The adhesive layer 6 is formed of a known adhesive such as an acrylic adhesive. The heater 10a is in contact with the adhesive layer 6 and is attached to the molded body 7 by the adhesive layer 6.

[0052] The adhesive layer 6 may be formed in advance on the main surface of the base material 2, for example. In this case, the heater 10a can be attached to the molded body 7 by pressing the heater 10a against the molded body 7 with the adhesive layer 6 facing the adherend surface 71. The adhesive layer 6 may also be covered with a separator (not shown). In this case, when the heater 10a is attached to the molded body 7, the separator is peeled off to expose the adhesive layer 6. The separator 6 is, for example, a film made of a polyester resin such as polyethylene terephthalate (PET).

[0053] The heater 10a is disposed on the optical path of near-infrared rays in, for example, an apparatus that performs processing using near-infrared rays. This apparatus performs a predetermined process, such as sensing or communication, using near-infrared rays. The molded body 7 constitutes, for example, a housing for such an apparatus. EXAMPLES

[0054] The present invention will be described in more detail below with reference to examples. Note that the present invention is not limited to the following examples. First, the evaluation methods and measurement methods for the examples and comparative examples will be described.

[0055] [Determination of the average maximum Feret diameter of grains] The laminates according to the examples and comparative examples were cut into square pieces of 300 μm square to obtain fragments. The fragments were fixed to a sample holder of an ultramicrotome so that the film surface of the transparent conductive film faced the operator. A knife was placed so that its tip was located on a plane that formed an extremely small acute angle (3° or less) with the film surface of the transparent conductive film in the fragment. The knife was then used to cut the fragments to a thickness of 70 nm to obtain slices. The knife was placed so that slices with a target observation area of ​​3 μm square or more could be obtained.

[0056] Using a transmission electron microscope JEM-2800 manufactured by JEOL, the film surface of the transparent conductive film in the sample for TEM observation prepared from the slice was observed. From the TEM photograph of this film surface, the boundaries between grains were determined based on the contrast difference between the images of adjacent grains in a field of view of 400 nm square at 10 or more randomly selected locations. Then, based on the boundaries between grains determined, the maximum Feret diameter of each grain contained in each field of view was determined. This determination was performed for grains that were entirely visible in each field of view. Based on the determined maximum Feret diameter of each grain, the average value Df of the maximum Feret diameter of the grains was determined by arithmetic average. The results are shown in Table 1. The maximum Feret diameter value of 10 or more grains was used to determine the average value Df of the maximum Feret diameter.

[0057] [Water vapor permeability measurement] Using a water vapor transmission rate measuring device DELTAPERM, the water vapor transmission rate of the test pieces for water vapor transmission rate measurement made from the laminates according to the examples and comparative examples was measured according to ISO 15106-5:2015. In this measurement, the temperature of the upstream chamber was adjusted to 40°C and the relative humidity was adjusted to 90%, and the pressure of the upstream chamber was adjusted to 50 Torr. In addition, in this measurement, the transparent conductive film was in contact with the downstream chamber. In this measurement, when the pressure of the downstream chamber exceeded 1 Torr, the vacuum pump was operated to perform evacuation. The water vapor transmission rate determined from the results of this measurement is shown in Table 1. The water vapor transmission rate of the substrates used in the examples and comparative examples was measured in the same manner as the laminates. The results are shown in Table 1.

[0058] [Measurement of the thickness of transparent conductive film] The thickness of the transparent conductive film of each of the laminates according to the examples and comparative examples was measured by X-ray reflectance method using an X-ray diffraction device (manufactured by Rigaku Corporation, product name: RINT2200). The results are shown in Table 1.

[0059] [Transparent conductive film density] The density of the transparent conductive film of each of the laminates according to the examples and comparative examples was measured according to the X-ray reflectance method. The results are shown in Table 1.

[0060] [Internal stress of transparent conductive film] Using an X-ray diffraction apparatus (Rigaku Corporation, product name: RINT2200), the sample was irradiated with Cu-Kα rays (wavelength λ: 0.1541 nm) from a 40 kV and 40 mA light source through a parallel beam optical system. 2 The internal stress (compressive stress) of the transparent conductive film was evaluated using the principle of the Ψ method. 2 The Ψ method is a method for determining the internal stress of a thin film from the dependence of the crystal lattice distortion of a polycrystalline thin film on the angle (Ψ). Using the above-mentioned X-ray diffraction device, the diffraction intensity was measured at 0.02° intervals in the range of 2θ = 29.8° to 31.2° by θ / 2θ scan measurement. The integration time at each measurement point was set to 100 seconds. The ITO crystal lattice plane spacing d at each measurement angle (Ψ) was calculated from the peak angle 2θ of the obtained X-ray diffraction (peak of the (222) plane of ITO) and the wavelength λ of the X-ray irradiated from the light source, and the crystal lattice distortion ε was calculated from the crystal lattice plane spacing d according to the relationship between the following formulas (1) and (2). λ is the wavelength of the X-ray (Cu-Kα line) irradiated from the light source, and λ = 0.1541 nm. d0 is the lattice plane spacing of ITO in a stress-free state, and d0 = 0.2910 nm. The value of d0 is that listed in the International Centre for Diffraction Data (ICDD) database. 2dsinθ=λ Equation (1) ε=(d-d0) / d0Equation (2)

[0061] As shown in Figure 6, the above-mentioned X-ray diffraction measurement was performed for each angle (Ψ) between the normal to the main surface of the transparent conductive film sample Sa and the normal to the crystal plane of the ITO crystal Cr of 45°, 52°, 60°, 70°, and 90°, and the crystal lattice distortion ε at each angle (Ψ) was calculated. Then, the residual stress (internal stress) σ in the in-plane direction of the transparent conductive film was calculated by sin 2 The relationship between Ψ and the crystal lattice distortion ε was plotted and the slope of the line was calculated using the following formula (3). The results are shown in Table 1. ε={(1+ν) / E}σsin 2 Ψ-(2ν / E)σ Equation (3)

[0062] In the above formula (3), E is the Young's modulus of ITO (116 GPa), and ν is the Poisson's ratio (0.35). These values ​​are as described in DG Neerinck and TJ Vink, “Depth Profiling of thin ITO films by grazing incidence X-ray diffraction”, Thin Solid Films, 278 (1996), pp. 12-17. In FIG. 6, a detector 100 detects X-ray diffraction.

[0063] [Durability test] A durability test was performed on the test pieces made from the laminates according to the examples and comparative examples. In the durability test, the test pieces were placed in an environment of 85°C temperature and 85% relative humidity for 1000 hours. Using a non-contact resistance measuring device (manufactured by Napson, product name: NC-80MAP), the sheet resistance of the transparent conductive film of each test piece was measured before and after the durability test by an eddy current measurement method in accordance with JIS Z 2316-1:2014. From the measurement results, the value of |Rp-Rb| / Rb was calculated for each test piece. Here, Rp is the value of the sheet resistance of the transparent conductive film after the durability test, and Rb is the value of the sheet resistance of the transparent conductive film before the durability test. Test pieces that satisfied |Rp-Rb| / Rb≦5% were evaluated as "A", and other test pieces were evaluated as "X". The results are shown in Table 1.

[0064] <Example 1> Using indium tin oxide (ITO) (tin oxide content: 10 wt%) as a target material, an ITO film was formed on a polyethylene naphthalate (PEN) film having a thickness of 125 μm by DC magnetron sputtering in the presence of an inert gas. Argon gas was used as the inert gas, and the pressure of the argon gas was adjusted to 0.2 Pa. The PEN film after the ITO film was formed was placed in the atmosphere at 180° C. for 1 hour to perform an annealing treatment. This caused the ITO to crystallize and form a transparent conductive film. In this way, a laminate according to Example 1 was obtained. The conditions of the DC magnetron sputtering method were adjusted so that the thickness of the transparent conductive film was 50 nm. A TEM photograph of the film surface of the transparent conductive film of the laminate according to Example 1 is shown in FIG. 7A. The boundaries between grains determined based on FIG. 7A are shown in FIG. 7B.

[0065] <Example 2> A laminate according to Example 2 was obtained in the same manner as in Example 1, except that the conditions of the DC magnetron sputtering method were adjusted so that the thickness of the transparent conductive film was 100 nm.

[0066] <Example 3> A laminate according to Example 3 was obtained in the same manner as in Example 1, except that a polyethylene terephthalate (PET) film having a thickness of 125 μm was used instead of the PEN film.

[0067] <Example 4> A laminate of Example 4 was obtained in the same manner as in Example 1, except that a PET film having a thickness of 125 μm was used instead of the PEN film and the annealing treatment conditions were changed to 1 hour in the atmosphere at 160° C.

[0068] <Example 5> A laminate according to Example 5 was obtained in the same manner as in Example 1, except that the conditions of the DC magnetron sputtering method were adjusted so that the thickness of the transparent conductive film was 30 nm.

[0069] <Comparative Example 1> A laminate according to Comparative Example 1 was obtained in the same manner as in Example 1, except that in the DC magnetron sputtering method, the argon gas pressure was changed to 0.45 Pa, and the PEN film after the ITO film was formed was placed in the atmosphere at 150° C. for 3 hours for annealing treatment. FIG. 8A shows a TEM photograph of the film surface of the transparent conductive film of the laminate according to Comparative Example 1. FIG. 8B shows the boundaries between grains determined based on FIG. 8A.

[0070] <Comparative Example 2> A laminate according to Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the argon gas pressure was changed to 1.0 Pa in the DC magnetron sputtering method.

[0071] <Comparative Example 3> Except for not carrying out the annealing treatment, a laminate according to Comparative Example 3 was obtained in the same manner as in Comparative Example 1. The transparent conductive film of the laminate according to Comparative Example 3 was amorphous.

[0072] As shown in Table 1, the transparent conductive films of the laminates according to Examples 1 to 5 had a small rate of change in sheet resistance before and after the durability test, suggesting that they exhibit good durability in a high-temperature, high-humidity environment. On the other hand, the transparent conductive films of the laminates according to Comparative Examples 1 to 3 had a large rate of change in sheet resistance before and after the durability test, suggesting that they do not have good durability in a high-temperature, high-humidity environment. In the transparent conductive films of the laminates according to Examples 1 to 5, the average maximum Feret diameter of grains was in the range of 160 to 400 nm, suggesting that this is advantageous in terms of durability in a high-temperature, high-humidity environment.

[0073] As shown in Table 1, the internal stress of the transparent conductive film in the laminates according to Examples 1, 2, and 5 was in the range of 100 to 500 MPa. On the other hand, the internal stress of the transparent conductive film in the laminates according to Examples 3 and 4 was larger than the internal stress of the transparent conductive film in the laminates according to Examples 1, 2, and 5. It was suggested that when a PET film was used as the substrate, shrinkage after annealing treatment was more likely to occur and the internal stress of the transparent conductive film was more likely to be large than when a PEN film was used as the substrate.

[0074]

Table 1

Claims

1. A transparent conductive film, The polycrystal has grains having an average maximum Feret diameter of 160 to 400 nm, the transparent conductive film maintains a water vapor transmission rate, determined in accordance with ISO 15106-5:2015, of 0.0010 to 0.0250 g / (m 2 ·24 hours) of a laminate in which the transparent conductive film is disposed on a support material; The water vapor transmission rate of the support material, determined according to ISO 15106-5:2015, is 1 g / (m2·24 h) or more. Transparent conductive film.

2. The transparent conductive film according to claim 1 , wherein the polycrystal contains indium oxide.

3. 7.15 g / cm 3 The transparent conductive film according to claim 1 or 2, having a density of at least 100%.

4. The transparent conductive film according to any one of claims 1 to 3, having a thickness of 20 to 150 nm.

5. 5. The transparent conductive film according to claim 1, wherein the internal stress of the transparent conductive film determined by X-ray stress measurement is 150 to 1000 MPa.

6. A substrate; The transparent conductive film according to any one of claims 1 to 5, which is disposed on the substrate. Laminate.

7. The water vapor transmission rate of the substrate, determined according to ISO 15106-5:2015, is 1 g / (m 2 The laminate according to claim 6, wherein the heat resistance is 24 hours or more.

8. forming a film on a substrate by sputtering; and annealing the film to form a polycrystalline transparent conductive film; In the sputtering, the pressure of the inert gas is adjusted to 0.4 Pa or less. A method for producing a transparent conductive film.

Citation Information

Patent Citations

  • Substrate with conductor

    JP1993151827A

  • Transparent electrically conductive film, transparent electrically conductive sheet and touch panel

    JP2002163932A

  • Transparent conductive film, and formation method of transparent conductive film

    JP2014201800A

  • Transparent conductive film and method for producing same

    WO2009157571A1

  • Transparent conductive film and method for producing same

    WO2015178298A1